Analysis of Land Use Changes and Land Value Zones Due to Phase 1 Mass Rapid Transit (MRT) Development in Menteng District, Central Jakarta - Muhammad Iqbal Adi Saputra; Citra Dewi; Fauzan Murdapa (Natural Sciences Engineering and Technology Journal, 2023)
The high demand for land in the area around the MRT station causes changes in land prices that tend to increase. These conditions can be the cause of changes in land use. This study used high-resolution images in 2021 and land use maps in 2014 and 2021. The data is used to analyze land-use changes. Meanwhile, the analysis of land value changes uses the 2014 land value zone map and the 2021 land value zone map obtained from the results of a field survey using the mass land valuation method. From these results, an analysis of the effect of changes in land use was carried out on changes in land value in Menteng District as a result of the construction of mass rapid transit phase 1. The results showed that there was a change in land use. The total area of ​​land change was 18.604 hectares or 2.879%. The details of the changes are trade increased by 1.362%, settlements decreased by 1.938%, hotels increased by 0.071%, lakes increased by 0.114%, vacant land decreased by 0.006%, parks increased by 0.368%, PT regularly increased by 0.485%, sports facilities decreased by 0.368% and government offices decreased by 0.088%. The highest price increase was Rp110,218,903/m2 because there was a change in land use from regular housing to trading areas. The largest increase in land value seen from the dominant land use characteristics was in commercial or trade areas, which was 187%, with an average increase in value of Rp. 76,170,137/m2.